Sacred Civics Building Seven Generation Cities - Engle, Jayne; Agyeman, Julian; Chung-Tiam-Fook, Tanya (Routledge Equity, Justice and the Sustainable City series, 2022)
Sacred Civics argues that societal transformation requires that spirituality and sacred values are essential to reimagining patterns of how we live, organize and govern ourselves, determine and distribute wealth, inhabit and design cities, and construct relationships with others and with nature. The book brings together transdisciplinary and global academics, professionals, and activists from a range of backgrounds to question assumptions that are fused deep into the code of how societies operate, and to draw on extraordinary wisdom from ancient Indigenous traditions; to social and political movements like Black Lives Matter, the commons, and wellbeing economies; to technologies for participatory futures where people collaborate to reimagine and change culture. Looking at cities and human settlements as the sites of transformation, the book focuses on values, commons, and wisdom to demonstrate that how we choose to live together, to recognize interdependencies, to build, grow, create, and love-matters. Using multiple methodologies to integrate varied knowledge forms and practices, this truly ground-breaking volume includes contributions from renowned and rising voices. Sacred Civics is a must-read for anyone interested in intersectional discussions on social justice, inclusivity, participatory design, healthy communities, and future cities.